The effects of ionized and nonionized compression garments on sprint and endurance cycling - Burden, R. J.; Glaister, M. (The Journal of Strength and Conditioning Research, 2012)
The aim of this study was to examine the effects of ionized and nonionized compression tights on sprint and endurance cycling performance. Using a randomized, blind, crossover design, 10 well-trained male athletes (age: 34.6 ± 6.8 years, height: 1.80 ± 0.05 m, body mass: 82.2 ± 10.4 kg, VO2max: 50.86 ± 6.81 ml/kg/min) performed 3 sprint trials (30-second sprint at 150% of the power output required to elicit VO2max [pVO2max] + 3 minutes recovery at 40% pVO2max + 30-second Wingate test + 3 minutes recovery at 40% pVO2max) and 3 endurance trials (30 minutes at 60% pVO2max + 5 minutes stationary recovery + 10-km time trial) wearing nonionized compression tights, ionized compression tights, or standard running tights (control). There was no significant effect of garment type on key Wingate measures of peak power (grand mean: 1,164 ± 219 W, p = 0.812), mean power (grand mean: 716 ± 68 W, p = 0.800), or fatigue (grand mean: 66.5 ± 6.9%, p = 0.106). There was an effect of garment type on blood lactate in the sprint and the endurance trials (p < 0.05), although post hoc tests only detected a significant difference between the control and the nonionized conditions in the endurance trial (mean difference: 0.55 mmol/L, 95% likely range: 0.1-1.1 mmol/L). Relative to control, oxygen uptake (p = 0.703), heart rate (p = 0.774), and time trial performance (grand mean: 14.77 ± 0.74 minutes, p = 0.790) were unaffected by either type of compression garment during endurance cycling. Despite widespread use in sport, neither ionized nor nonionized compression tights had any significant effect on sprint or endurance cycling performance.